Role of Financial Reporting on Carbon Emissions in Enhancing the Relevance of Accounting Information - Tuama Kudair *, Sana; Zaid Ibrahim, Lubna (Journal of Economics and Administrative Sciences, 2024)
In an effort to enhance the applicability of accounting data for international oil corporations operating in Iraq, this study delves into the role of Financial Reporting on Carbon Emissions (FRCE). The researchers explore the overarching concept and significance of the Relevance of Accounting Information (RAI) in general, with a specific focus on its application to accounting information related to carbon emissions. The study also addresses the financial reporting of carbon emissions in industrial companies. Using two mathematical models, namely the Informational Content Model (ICM) and Autoregressive Integrated Moving Average (ARIMA), the researchers conduct an in-depth analysis of eleven years’ worth of financial statements from Dana Gas, forming the basis of this study’s sample. The analysis is performed using SPSS. Several conclusions have emerged from the study, with a pivotal finding being that ensuring the relevance of accounting information related to carbon emissions aligns with both user requirements for accounting information and the imperatives of environmental preservation. Moreover, the study underscores the impact of financial reporting on carbon emissions programs and greenhouse gas emissions on the relevance of accounting information, thereby influencing the overall quality of financial reporting. The study highlights that enhancing the suitability of information through financial reporting on carbon emissions contributes significantly to elevating the standard of financial reporting for the firm. As a recommendation, the researchers advocate for compliance with local laws or international treaties regulating carbon emissions, emphasizing the inclusion of accounting information and financial reports detailing expenses associated with carbon emissions in these compliance efforts. Paper type Research paper